A felekezeti struktúra változása Kelet- és Közép-Európában (Szociológiai Szemle, 2024)
The paper studies the Catholic-Protestant presence in the contemporary East Central Europe. While doing so, it unites two approaches of the sociology of religions. The first one is interested in the structure of denominations and trends of its changes. The second one seeks to find the role of religion and identity by religious denomination in the East European systemic change. The issue how the following of the different churches and their relative proportion changed during the decades of socialist and communist system, emerges at the meeting point of the two schools. The paper studies the recent data of three such countries where the Catholic, as well as Protestant population has had significant proportions: Czechoslovakia (the Czech Republic as well as Slovakia), Latvia and Hungary. The data uniformly show the absolute and relative decrease of the proportion of Protestants and the growth of the Catholic ones. The results of comparison in time are corroborated by and offer possibilities to further inferences when the data of groups of different school education, and of religious commitments of different strength are collated. Finally the paper outlines hypotheses related to shifts in proportions.